The Influence of The Human Development Index, Unemployment Rate, and Illiteracy Population on Poverty Level in Indonesia for the Period 2015-2020 - Ipmawan, Hasan; Kristanto, Dwi; Hendrawan, Koen; Kuncoro, Aris Wahyu (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
Unemployment and poverty are issues that require serious and systematic solutions. So far, the human development index, unemployment rate, and illiteracy rate have dominated. This study looks into how the Human Development Index affects poverty in Indonesia. Second, examine the impact of Unemployment on poverty in Indonesia. Third, examine the impact of Illiteracy on poverty in Indonesia. The Stepwise technique was chosen in this study because it provides information on the independent variables that influence the dependent variable. The Human Development Index, Education Level, and Illiteracy Population were studied sequentially. This study employed secondary data. The statistics were gathered from third sources and are available at the Central Statistics Agency (BPS). The research shows that the three variables are directly associated with poverty in Indonesia. Less effective programs tend to be partial. So, as a policymaker, the government must start an integrated program focusing on the three points mentioned.